The Impact of COVID-19 on Immigrants and Refugees Living with Mental Health and Addiction Disorders: A Population-Based Cohort Study in Ontario, Canada - Vahabi, Mandana; Koh, Maria; Wong, Josephine Pui-Hing; Palma, Luis; Kopp, Alexander; Lofters, Aisha K. (Archives of Clinical and Biomedical Research, 2024)
Background: While the COVID-19 pandemic has taken an enormous toll on communities across Canada and the globe, its negative impacts have not been experienced equally. People with mental health and addiction disorders (MH&A) have been found to be at greater risk of COVID-19 infection and worse COVID-19 outcomes. Similarly, although immigrants and refugees contribute to one-quarter of Ontario’s population they make up nearly half of Ontario’s COVID-19 cases. There is a paucity of information on the impact of COVID-19 on people who are at the intersection of MH&A and socioeconomic deprivation. Our study aimed to address this gap. Methods: A population-based retrospective cohort study over a oneyear period (January 15, 2020, to Feb 15, 2021) was conducted using multiple linked provincial-administrative databases. The study aimed to determine the differential impact of COVID-19 on immigrants and nonimmigrants and refugees with MH&A and the general population without MH&A across sociodemographic and health-related factors like age, sex, neighbourhood income, Ontario marginalization index, comorbidities, and access to primary care. We used multivariable regression to adjust for potential confounders. Results: Our cohort comprised 10,994,464 Ontario residents aged 18 or older and of which approximately 17% lived with MH&A, with immigrants and refugees with MH&A making up 2.6%. People with preexisting MH&A were generally younger and more likely to live in deprived neighbourhoods compared to the general population. Immigrants and refugees with MH&A were more likely to reside in neighbourhoods with greater material deprivation, residential instability, and ethnic concentration compared to non-immigrants with MH&A. Even though the COVID-19 testing rate was lower among immigrants living with MH&A compared to non-immigrants with MH&A (32.7% vs. 37.6%), the confirmed positivity was significantly higher (12.4% vs. 4.5%). Adjusting for confounders we also found Covid 19 testing, hospital admission, intensive care admission, and mortality rates related to COVID-19 were considerably higher among people with MH&A than in the general population. Conclusion: Our findings provide evidence of the need to accelerate the development of targeted evidence-based policies that can effectively support and protect people living at the intersection of clinical and social inequities in this and future crises.